The Cambridge introduction to modern Irish poetry, 1800-2000 - Quinn, Justin (Cambridge University, 2013)
Over the last two centuries, Ireland has produced some of the world's most outstanding and best loved poets, from Thomas Moore to W. B. Yeats to Seamus Heaney. This introduction not only provides and overview of the history and development of poetry in Ireland, but also offers new approaches to the field. This book offers a contextual background and pays attention to the major poems and poets.